Expanding Psychiatric Ethics - Person, Ethel Spector (The Hastings Center report, 1982)
Book reviewed in this article: Philosophy in Medicine: Conceptual and Ethical Problems in Medicine and Psychiatry. By Charles M. Culver and Bernard Gert. Psychiatric Ethics. Edited by Sidney Block and Paul Chodoff. Man, Mind, and Morality: The Ethics of Behavior Control. By Ruth Macklin.